Online educational intervention: Improving maternal knowledge and attitudes in providing developmental stimulation for stunting toddlers - Faridah, Faridah; Anies, Anies; Kartasurya, Martha I.; Widjanarko, Bagoes (Narra Sains Indonesia, 2024)
Stunting remains a significant public health concern, impacting physical growth and impeding children's development. Mothers, who play a crucial role in stimulating children's development, often encounter barriers in providing effective stimulation, primarily due to limited access to appropriate resources and information. Online education can bridge this gap by offering easily accessible learning. This aim of this study was to determine the effect of online education on maternal knowledge and attitudes in providing developmental stimulation for stunting toddlers. A quasi-experimental research design was employed, comprising a treatment group and a control group, each consisting of 46 mothers with stunting toddlers, sampled purposively. The treatment group received an online developmental stimulation educational intervention through WhatsApp groups for twelve meetings, each lasting 1.5 to 2 hours. Meanwhile, the control group participated in a stunting assistance program provided by the community health centers (Puskesmas). To compare the knowledge and attitudes between groups, Mann-Whitney and independent Student t-test were used. The assessment of intervention effects on knowledge and attitudes was conducted using Wilcoxon and paired Student t-test within each group. Following the educational intervention on developmental stimulation, there was a significant increase in knowledge; however, there was no significant difference in attitudes. The treatment group (mean score 3.9±1.76) had a higher increase in knowledge scores compared to the control group (2.0±2.25) with a p<0.001. Nonetheless, no significant difference in attitudes was observed between the two groups with the mean change scores was 5.8±15.31 in treatment group and 2.5±18.69 for control group, with a p=0.335. This study suggests that providing online education leads to increased knowledge scores but does not impact attitudes significantly. Additional educational approaches should be considered to enhance maternal attitudes.